The Impact of Early Deafness on Brain Plasticity: A Systematic Review of the White and Gray Matter Changes - Simon, Marie; Campbell, Emma; Genest, François; MacLean, Michèle W.; Champoux, François; Lepore, Franco (Frontiers in Neuroscience, 2020)
Background: Auditory deprivation alters cortical and subcortical brain regions, primarily linked to auditory and language processing, resulting in behavioral consequences. Neuroimaging studies have reported various degrees of structural changes, yet multiple variables in deafness profiles need to be considered for proper interpretation of results. The purpose of this study was to provide the first systematic review synthesizing grey and white matter changes in deaf individuals. Methods: We conducted a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA) in 27 studies comprising 626 deaf individuals. Results: Evidence shows that auditory deprivation significantly alters white matter across the primary and secondary auditory cortex. The most consistent alteration across studies was in the bilateral superior temporal gyri. Furthermore, plasticity linked to changes in grey matter, appears to be related to enhanced performance during sensory and cognitive processing. The reviewed studies also suggest that grey and white matter integrity is sensitive to early sign language acquisition, attenuating the effect of auditory deprivation on neurocognitive development. Conclusions: These findings suggest that understanding cortical reorganization through grey and white matter changes is an important factor in the development of auditory rehabilitation strategies in the deaf population.